Obstructive sleep apnoea and adherence to continuous positive airway therapy among Australian women. Issue 3 (20th March 2022) - Heraganahally, Subash S.; Zaw, Kyi K.; Tip, Sai; Jing, Xinlin; Mingi, Joy J.; Howarth, Timothy; Roy, Anil; Falhammar, Henrik; Sajkov, Dimitar
Abstract: Background: Clinical characteristics of women with different obstructive sleep apnoea (OSA) severity and adherence to continuous positive airway pressure (CPAP) therapy have not been previously explored. Aims: To assess OSA prevalence, predictors, clinical and polysomnographic (PSG) characteristics and adherence to CPAP therapy among adult Australian women in a retrospective study. Methods: All female patients who underwent a diagnostic PSG between 2014 and 2015 were included. CPAP adherence was assessed during the study period between 2018 and 2019 using multiple regression models. Results: Among a total of 591 women included in this study (Aboriginal, n = 86), OSA was diagnosed in 458/591 (78%) patients; mild, moderate and severe OSA was present in 44%, 27% and 29% respectively. Older age, higher BMI and hypertension predicted the presence and severity of OSA. The Epworth Sleepiness Scale (ESS) score was not significantly different with (8 (5, 12)) or without (10 (5, 13)) OSA. PSG showed the rapid eye movement (REM) sleep‐associated apnoea−hypopnea index (AHI) was higher with all severity of OSA. Adherence to CPAP therapy was noted in 171 (57%) patients; 47% mild, 57% moderate and 63% with severe OSA respectively. Three multiple regression models (clinical, PSG parameters, OSA severity, combined (clinical and PSG)) showed the combined model had the strongest predictive value and demonstrated that higher ESS and more severe oxygen desaturation were associated with CPAP adherence irrespective of OSA severity. Conclusions: Older age, higher BMI and the presence of hypertension predicted the presence of OSA. The REM sleep‐related AHI was higher. Adherence to CPAP was associated with symptomatic OSA and severe oxygen desaturation.